2016
DOI: 10.1111/1541-4337.12201
|View full text |Cite
|
Sign up to set email alerts
|

Biologically Active Compounds from Hops and Prospects for Their Use

Abstract: Although female cones of the hop plant (Humulus lupulus) are known primarily as raw material supplying characteristic bitterness and aroma to beer, their equally significant health-promoting effects have been known to mankind for several thousand years and hop is a plant traditionally utilized in folk medicine. This paper summarizes the scientific knowledge on the effects of all 3 major groups of secondary metabolites of hops; polyphenols, essential oils, and resins. Because of their chemical diversity, it is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
200
0
23

Year Published

2016
2016
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 201 publications
(226 citation statements)
references
References 295 publications
(393 reference statements)
3
200
0
23
Order By: Relevance
“…Hop polyphenols comprise almost 4% of the total hop cone dry mass, and they belong to a wide range of classes, including flavonols, flavanols, prenylated chalcones and flavanones, but also phenolic acids, stilbenes and phloroglucinol derivatives [3,4]. It has been reported that more than 100 different compounds may occur in hop extracts, their profile depending mainly on varietal parameters, lending hop an important prospect as a medicinal plant [5,6].…”
Section: Introductionmentioning
confidence: 99%
“…Hop polyphenols comprise almost 4% of the total hop cone dry mass, and they belong to a wide range of classes, including flavonols, flavanols, prenylated chalcones and flavanones, but also phenolic acids, stilbenes and phloroglucinol derivatives [3,4]. It has been reported that more than 100 different compounds may occur in hop extracts, their profile depending mainly on varietal parameters, lending hop an important prospect as a medicinal plant [5,6].…”
Section: Introductionmentioning
confidence: 99%
“…Xanthohumol exhibits many bioactive effects against cancer, diabetes, hepatitis C and HIV‐1 viruses, malaria parasites, etc. .…”
Section: Introductionmentioning
confidence: 99%
“…During brewing process, gallic, caffeic, p‐coumaric, and ferulic acids increased in HW, after the addition of hop. Phenolic acids in hop comprise 3–6% of the dry weight of hop cones (Karabín et al .,). It is known that in barley beer, both malt and hops are sources of beer polyphenol substances (Lentz, ).…”
Section: Resultsmentioning
confidence: 99%